Financial Ratio in the Analysis of Earnings Management - Irma Christiana; Nadia Ika Purnama; Isna Ardila (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2020)
Earnings management is an action taken by company management to influence reported earnings. The purpose of this study is to analyze earnings management of Perum Perumnas Regional I Medan by using financial ratios, namely leverage ratios and profitability ratios for the period 2014-2017. Earnings management in this study is proxied by discretionary accrual (DA) and measured using the Jones Modified Model. While the leverage ratio is proxied by the debt to assets ratio (DAR) and profitability ratio is proxied by the return on assets ratio (ROA). This study uses quantitative data and data is collected by documentation techniques. Data analysis techniques used descriptive analysis based on time series methods. The results of the study concluded that Perum Perumnas Regional I Medan practices earnings management with a pattern of increasing profits in 2014, 2016 and 2017. Earnings management practices are motivated because of high leverage values. While profitability does not motivate managers to practice earnings management, because high or low profitability generated by the company is ignored by investors. Keywords: earnings management, leverage, profitability